Thalidomide Attenuates Skin Lesions and Inflammation in Rosacea-Like Mice Induced by Long-Term Exposure of LL-37 - Kang Y; Zhang C; He Y; Zhang Z; Liu H; Wei Z; Yang J (Dove Medical Press, 2022)
Yumeng Kang,1 Chuanxi Zhang,1 Yang He,1 Ziyan Zhang,1 Heliang Liu,2 Zhongqiu Wei,3 Jie Yang1 1Department of Dermatology, Affiliated Hospital of North China University of Science and Technology, Tangshan, People's Republic of China; 2Hebei Key Laboratory for Organ Fibrosis Research, School of Public Health, North China University of Science and Technology, Tangshan, People's Republic of China; 3School of Basic Medical Sciences, North China University of Science and Technology, Tangshan, People's Republic of ChinaCorrespondence: Zhongqiu Wei, School of Basic Medical Sciences, North China University of Science and Technology, 21 Bohai Avenue, New City, Caofeidian District, Tangshan City, Hebei Province, People's Republic of China, Tel +86-135-8258-8338, Email weizhongqiu@ncst.edu.cn Jie Yang, Department of Dermatology, Affiliated Hospital of North China University of Science and Technology, 73 Jianshe South Road, Lubei District, Tangshan City, Hebei Province, People's Republic of China, +86-188-3250-6999, Email yjj1971321@163.comPurpose: Most of the existing studies focus on the early inflammation of rosacea, with few interventions on the later development of fibrosis and the relationship between thalidomide and rosacea. The purpose of this study was to construct a long-term induction model and explore the effects of thalidomide on the later stage of inflammation and early stage of fibrosis in rosacea.Patients and Methods: BALB/c male mice were randomly divided into four groups: control group, control plus thalidomide group, LL-37 group and LL-37 plus thalidomide group, Intradermal and intraperitoneal injections were given. After repeated induction, skin changes were recorded by taking photos. The animals were sacrificed, the back skin was used for HE staining and VG staining to detect histomorphological characteristics. Immunofluorescence staining and Western blot were used to detect the expression of inflammatory and fibrosis-related factors.Results: The results were compared with the early stage of the model, wherein the skin inflammation of the 20-day mice was more obvious with a trend of fibrosis. Compared with the control group, histopathological examination showed that the inflammatory cell infiltration in the LL-37 group was significantly increased, and the skin was thickened with collagen deposition. LL-37 induction significantly increased the expression of inflammatory markers (eg, TNF-α and IL-1β) and fibrotic markers (eg, COL1, α-SMA, vimentin and N-Cadherin). Intervention with thalidomide significantly reduced erythema, inflammatory cell infiltration, collagen deposition, and down-regulate the expression of inflammation and fibrosis related factors in rosacea mice.Conclusion: The long-term continuous induction of LL-37 in mice could simulate the occurrence and development of rosacea, and thalidomide could ameliorate the rosacea induced by long-term exposure to LL-37 by regulating inflammatory infiltration, collagen deposition and fibrosis-related processes.Keywords: rosacea, LL-37, thalidomide, inflammation, skin fibrosis